2018
DOI: 10.1016/s2215-0366(18)30057-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventive strategies for mental health

Abstract: Available treatment methods have shown little effect on the burden associated with mental health disorders. We review promising universal, selective, and indicated preventive mental health strategies that might reduce the incidence of mental health disorders, or shift expected trajectories to less debilitating outcomes. Some of these interventions also seem to be cost-effective. In the transition to mental illness, the cumulative lifetime effect of multiple small effect size risk factors progressively increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
383
0
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 512 publications
(410 citation statements)
references
References 117 publications
(183 reference statements)
5
383
0
22
Order By: Relevance
“…In young adults, Fonseca‐Pedrero et al () found that the “High schizotypy” class scored higher on mental distress, hypomanic experiences and anticipatory and consummatory pleasure relative to non‐risk latent classes. It is relevant to note that those subgroups of participants potentially at high risk for psychosis, plus suicide ideation, affective symptoms and/or distressing PLEs may require attention; for instance, could benefit from further comprehensive assessments (eg, clinical interview) in order to analyse their mental health status and developmental trajectories as well as to implement prophylactic preventive interventions (Arango et al, ; McGorry, Hartmann, Spooner, & Nelson, ). It would be particularly relevant to detect those adolescents at risk of suicide behaviour, due to the personal, clinical, and societal implications involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young adults, Fonseca‐Pedrero et al () found that the “High schizotypy” class scored higher on mental distress, hypomanic experiences and anticipatory and consummatory pleasure relative to non‐risk latent classes. It is relevant to note that those subgroups of participants potentially at high risk for psychosis, plus suicide ideation, affective symptoms and/or distressing PLEs may require attention; for instance, could benefit from further comprehensive assessments (eg, clinical interview) in order to analyse their mental health status and developmental trajectories as well as to implement prophylactic preventive interventions (Arango et al, ; McGorry, Hartmann, Spooner, & Nelson, ). It would be particularly relevant to detect those adolescents at risk of suicide behaviour, due to the personal, clinical, and societal implications involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to gain a deeper understanding in the identification of psychosis liability groups at population level and its links with psychopathology. This research may allow us to improve our knowledge about tentative etiological mechanisms as well as risk and protective factors in order to develop prevention strategies (Arango et al, ). Reliable identification of individuals at‐high risk and timely prophylactic intervention may delay, ameliorate or prevent the onset of frank psychotic symptoms, as well as reduce its possible impact on many levels (Barrantes‐Vidal et al, ; Fusar‐Poli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, se ha mostrado que es un error pensar que los programas tendrán efectos específicos sobre cada trastorno, dado que iguales determinantes pueden dar lugar a consecuencias y trastornos diferentes; asimismo, un problema o trastorno de salud mental particular puede tener distintas causas (equipotencialidad y multifinalidad, respectivamente) (Toth, Petrenko, Gravener Davis y Handley, 2016). En consecuencia, es probable que los programas tengan efectos más amplios que la sola reducción de la incidencia de un tipo de trastorno particular (Arango et al, 2018;Cuijpers, 2011).…”
Section: Investigación En Promoción Y Prevención En Salud Mentalunclassified
“…Al respecto, debe pensarse que la instalación de procedimientos de tamizaje y detección temprana puede extenderse a una diversidad de áreas, y, de hecho, así aparece sugerido en las propuestas de los equipos que trabajan en el tema. Una revisión reciente que incluye las diversas opciones de tamizaje y detección que podrían ya implementarse o que ya lo están siendo muestra lo que podría transformarse en un clima de vigilancia continua: tamizaje por historia familiar de trastornos mentales; tamizaje de variantes genéticas asociadas con un incremento de riesgo de fenotipos neurocognitivos y psiquiátricos; tamizaje de de-FÉLIX COVA SOLAR, PAMELA GRANDÓN FERNÁNDEZ, SANDRA SALDIVIA BORQUEZ, CAROLINA INOSTROZA ROVEGNO Y CONSUELO NOVOA RIVERA presión postnatal; tamizaje y vigilancia de trayectorias de desarrollo; detección de retraso o alteraciones de hitos del desarrollo; detección de irritabilidad crónica, hiperactividad y declinación cognitiva; detección de conducta social alterada, resultados escolares insuficientes, experiencias de tipo psicótico; detección de biomarcadores cerebrales o sanguíneos (Arango et al, 2018). Los efectos iatrogénicos que puede generar un clima de hipervigilancia derivados de un uso masivo o indiscriminado de tamizajes y procedimientos de detección temprana pueden ser acentuados por otros factores.…”
Section: Promoción Y Prevención De La Salud Mental Y Medicalizaciónunclassified
See 1 more Smart Citation